Konstruksi Kompetensi Pedagogik Guru dalam Pembelajaran: Construction of Teacher Pedagogic Competence in Learning - Solihin, Rahmat; Iqbal, Muhammad; Muin, Muhammad Tamsil (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2021)
Pedagogical Content Knowledge is a concept in education research which was first initiated by Shulman in 1986. The PCK concept seeks to uncover the teacher competence construct to produce quality learning. By using library research, the authors search for relevant reference regarding PCK as primary data in this study. The author concludes that PCK is a combination of teacher knowledge about pedagogy and teacher knowledge about content or learning subjects. These two competencies are interrelated and reinforce each other so that neither one nor both can be left out. A teacher must understand what he teaches before he teaches the knowledge to his students. This is what distinguishes a teacher from a scientist who focuses on developing knowledge, while the teacher focuses more on transforming the delivery of knowledge to students.